An approach to bank insolvency in transition and emerging economies - David G. Mayes (Bank of Finland, 2004)
In the light of the inequity of the way losses from bank insolvencies and their avoidance through intervention by the authorities have been distributed over creditors, depositors, owners and the population at large in transition and emerging economies, this paper explores a number of regulatory reforms that would alter the balance between seeking to avoid insolvency and lowering the costs of insolvency should it occur.In particular it considers whether a lex specialis for dealing with banks that are in trouble through prompt corrective action and if necessary resolving them if their net worth falls to zero, at little or no cost to the taxpayer can be applied in the institutional framework of transition and emerging economies.
URN:NBN:fi:bof-20140807124
Keywords: K23; G21; O16; G28; 330; insolvency; banks; transition; emerging economies